The Wax Ancient Historical Citadel: An exploratory field study - Fadlallah, Jaafar Zouheir (Journal of Humanities & Social Sciences, 2021)
Choosing the location of the big & small citadels & distributing them inside & outside Lebanon is undoubtedly mainly connected with geographic & strategic elements. If we consider these citadels geographically & look at their distribution & the way they are spread, we will notice the importance of the location where they have been built especially the Wax Citadel which is located in the south of Lebanon near the Lebanese & Palestinian border lines! This citadel is located at the highest area in the Wax country. It is 380 meters higher than sea level. It overlooks the cities & villages of Tyre & Bint Jubail from the East , overlooks the Palestinian Plain from the South , & the Lebanese Plain extending from the North to Tyre City to the Palestinian borders in the South. Similarly, it overlooks AlBayyada plains, Mina Iskandaroun, & Ras Al Naqoura. With respect to the naming of the country, this is related to the Wax/ Shama’ naming of the citadel as well as of the country; it is related to the religious shrine situated at the highest place of the country near the citadel.This shrine is known as the Shrine of the prophet Shamaoun Al Safa. However, other studies claim that this citadel has been named as the Citadel of Iskandaron related to the sea port called Iskandaron which is situated at the head entrance of Al Bayyada & the road which leads to the(Wax) or Shama’ country. Another study carried out by Mr Abdul Rahman Al Zaki claims for the first time that this Citadel is called Scanalium Citadel. With respect to the history of the citadel, this is still relatively unknown similar to other ancient ruins in Lebanon which are still unknown up to a certain extent. This is because of the absence of really specialised studies in this field, or the absence of excavations of ruins to stop the argument in this domain about this issue. This is why I shortened the information about this issue. I think it goes back to the crusaders era. I gave touristic information which is transferred every now & then, but it sometimes disappears. This aroused my interest to carry a deeper field action research depending on my humble experience in the science of ruins or Field of Archeology.